SEISMIC IMAGING OF LITHOSPHERIC DISCONTINUITIES AND CONTINENTAL EVOLUTION - Bostock M.G. (My University, 1999)
Discontinuities in physical properties within the continental lithosphere reflect a range of processes that have contributed to craton stabilization and evolution. A survey of recent seismological studies concerning lithospheric discontinuities is made in an attempt to document their essential characteristics. Results from long-period seismology are inconsistent with the presence of continuous, laterally invariant, isotropic boundaries within the upper mantle at the global scale. At regional scales, two well-defined interfaces termed H (~ 60 km depth) and L (~ 200 km depth) of continental affinity are identified, with the latter boundary generally exhibiting an anisotropic character. Long-range refraction profiles are frequently characterized by subcontinental mantle that exhibits a complex stratification within the top 200 km. The shallow layering of this package can behave as an imperfect waveguide giving rise to the so-called teleseismic Pn phase, while the L-discontinuity may define its lower base as the culmination of a low velocity zone. High-resolution, seismic reflection profiling provides sufficient detail in a number of cases to document the merging of mantle interfaces into lower continental crust below former collisional sutures and magmatic arcs, thus unambiguously identifying some lithospheric discontinuities with thrust faults and subducted oceanic lithosphere. Collectively, these and other seismic observations point to a continental lithosphere whose internal structure is dominated by a laterally variable, subhorizontal layering. This stratigraphy appears to be more pronounced at shallower lithospheric levels, includes dense, anisotropic layers of order 10 km in thickness, and exhibits horizontal correlation lengths comparable to the lateral dimensions of overlying crustal blocks. A model of craton evolution which relies on shallow subduction as a principal agent of craton stabilization is shown to be broadly compatible with these characteristics. © 1999 Elsevier Science B.V. All rights reserved.
Keywords: CONTINENTAL EVOLUTION; CRATON STABILIZATION; LITHOSPHERIC DISCONTINUITY; SEISMIC IMAGING